Effect of Soaking in Chicken Eggshell Solution on Tooth Enamel Hardness - Mila D. Yurisya; Diah A. Purbaningrum; Donna Hermawati; Gloria Fortuna (e-GiGi, 2022)
Abstract: Eggshell is one of the natural wastes which if not treated properly can cause environ-mental pollution. Broiler eggshells consist mostly of CaCO3 (calcium carbonate) that can be synthesized into CaO (calcium oxide) then be processed into Ca (calcium). Calcium has a function to fill the density of bones and teeth that affects their strength and hardness. This study aimed to determine the effect of soaking in broiler chicken eggshell solution on the hardness of tooth enamel. This was an experimental laboratory study with a posttest only control group design. Samples were 24 maxillary first premolar obtained from dental clinics, public health centers, and hospitals in Semarang, Indonesia. Samples were divided into four groups: control group and treatment groups 1, 2, and 3 (duration of soaking in eggshell solution for 2, 7, and 14 days. respectively). The one way ANOVA test resulted in a p-value of 0.000 which meant that there were significant differences in the four groups. The post hoc test showed a p-value of <0.05, which meant that there was a significant difference between the control group (artificial saliva) and the treatment groups of 2.7 and 14 days. In conclusion, chicken eggshell solution has an effect on increasing the hardness of tooth enamel.Keywords: tooth enamel; hardness of tooth enamel; chicken eggshell Abstrak: Cangkang telur merupakan salah satu limbah alam yang apabila tidak diolah dengan baik dapat menyebabkan pencemaran lingkungan. Komposisi cangkang telur ayam ras sebagian besar terdiri dari CaCO3 (kalsium karbonat) yang dapat disintesis menjadi CaO (kalsium oksida) dan selanjutnya diolah menjadi Ca (kalsium). Kalsium memiliki fungsi untuk mengisi kepadatan tulang dan gigi yang memengaruhi kekuatan serta kekerasannya. Penelitian ini bertujuan untuk mengetahui pengaruh perendaman larutan cangkang telur ayam ras terhadap kekerasan enamel gigi. Jenis penelitian ialah eksperimental laboratorik dengan posttest only control group design. Sampel penelitian ialah 24 gigi premolar satu rahang atas yang didapatkan dari klinik praktek dokter gigi, puskesmas dan rumah sakit di Kota Semarang. Sampel dibagi atas empat kelompok: kelompok kontrol dan kelompok perlakuan 1, 2, dan 3 (perendaman dalam larutan cangkang telur ayam ras selama 2, 7, dan 14 hari berturut). Hasil uji ANOVA one way memperoleh nilai p=0,000 yang berarti bahwa terdapat perbedaan bermakna pada keempat kelompok. Uji post hoc menunjukkan nilai p<0,05 yang berarti terdapat perbedaan bermakna antara kelompok kontrol (perendaman saliva artificial) dan kelompok perlakuan (perendaman larutan cangkang telur ayam ras 2, 7 dan 14 hari). Simpulan penelitian ini ialah perendaman dalam larutan cangkang telur ayam ras berpengaruh dalam peningkatan kekerasan enamel gigi.Kata kunci: enamel gigi; kekerasan enamel gigi; cangkang telur ayam ras